International diversification benefits with foreign exchange investment styles - Tim Alexander Kroencke; Felix Schindler; Andreas Schrimpf (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
This paper provides a comprehensive analysis of portfolio choice with popular foreign exchange (FX) investment styles such as carry trades and strategies commonly known as FX momentum, and FX value. We investigate if diversification benefits can be achieved by style investing in FX markets relative to a benchmark allocation consisting of U.S. bonds, U.S. stocks, and international stocks. Overall, our results suggest that there are significant improvements in international portfolio diversification due to style-based investing in FX markets (both in the statistical, and most importantly, in the economic sense). These results prevail for the most important investment styles after accounting for transaction costs due to re-balancing of currency positions, and also hold in out-of-sample tests. Moreover, these gains do not only apply to a mean-variance investor but we also show that international portfolios augmented by FX investment styles are superior in terms of second and third order stochastic dominance. Thus, even an investor who dislikes negatively skewed return distributions would prefer a portfolio augmented by FX investment styles compared to the benchmark.
Keywords: G11; G12; G15; 330; International Diversification; Foreign Exchange Speculation and Hedging; Carry Trades; Stochastic Dominance; Investment Styles